In situ IR - TPD study of the synthesis of C3-oxygenates from propylene partial oxidation over a Rh/Al2O3 catalyst - Singh, Rahul; Chuang, Steven; Khatri, Rajesh (Ciencia)
Propylene partial oxidation over Rh/Al2O3 produced CO2 as well as C3 oxygenates (i.e., acetone, isopropanol. and propanal) at 250°C. In situ infrared spectroscopic study revealed that the formation of CO2 led those of C3 oxygenates, suggesting that CO2 and C3 oxygenates were formed via independent pathways. In the partial oxidation pathway, acetone was produced and further hydrogenated to isopropanol by hydrogen on the Rh surface. Propanal was formed from a separate pathway and strongly adsorbed on the catalyst surface. The C3 oxygenates can be further oxidized to a stable carboxylate intermediate. The slow rate of change in the IR intensive remer factor of the carboxylate under transient conditions suggests that the carboxylate is a spectator intermediate in propylene partial oxidation. The infrared spectroscopy observation of linear CO on RhÂº site suggests that the reduced Rh site plays an important role in propylene partial oxidation.